The Holy Veil: Hijab as a Fluid Signifier of Agency and Oppression in The Holy woman: https://doi.org/10.55966/assaj.2025.4.1.044 - Ch Muhammad Uzair Chohan; Syed Anas Jan (`, 2025)
This study delves into the symbolic and performative aspects of the hijab in Qaisra Shahraz's novel The Holy Woman, examining how the veil serves as a fluid signifier of both empowerment and subjugation. Drawing on Judith butler's theory of gender performativity and the principles of Islamic feminism, the study interrogates the ways in which veiling is socially constructed, imposed, and eventually reappropriated by the female protagonist, Zarri Bano. Initially employed as a means of patriarchal control after she was designated as a 'holy woman,' the hijab becomes a contested space where cultural tradition, religious devotion, and personal autonomy converge. Through close textual analysis, the research reveals that Shahraz complicates dominant western and traditionalist Islamic narratives of the veil, portraying it not as a fixed symbol but as one who’s meaning shifts according to context, choice, and power. The study adds to the ongoing conversation in feminist literature by emphasizing how religious and cultural symbols can be reimagined and reclaimed by women as a means of challenging oppressive systems. Keywprds: Hijab, Agency, Oppression, The Holy Woman, Gender Representation